Carbon-based silicon dioxide composite material, high-impact low-VOC (volatile organic compound) resin composite material as well as preparation method and application thereof
By synthesizing SiO2 in situ and carrying out hydrothermal carbonization in the liquid phase system, a carbon-based silica composite material with high specific surface area and superior adsorption properties was prepared, which solved the problem of poor structural stability of composite materials in the prior art, and significantly improved the VOC release and impact resistance of the resin material.
Patent Information
- Application Number
- CN202311146295.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-09-06
AI Technical Summary
In the prior art, the simple mixing preparation of carbon-based materials and SiO2 results in poor structural stability of composite materials, limiting the improvement of material performance and affecting its use range.
In the liquid phase system, SiO2 is synthesized in situ on the carbon source using carbon source and silicon source as raw materials to form a composite containing carbon source and SiO2, and then hydrothermal carbonization is carried out to prepare a composite component containing SiO2 and activated carbon fiber.
The prepared carbon-based silica composite material has a high specific surface area and excellent adsorption properties, which can significantly improve the VOC release of the resin material and improve its impact resistance.
Smart Images

Figure CN119565565A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of organic-inorganic composite fillers for resins, and more particularly to carbon-based silicon dioxide composite materials, high-impact and low-VOC resin composite materials, and preparation methods and applications thereof. Background Art
[0002] At present, people are paying more and more attention to the environmental performance of materials. The organic gas released by polymer materials during use is one of the important data for environmental monitoring. Therefore, it is a general trend to develop low-VOC resins with the goal of energy conservation, emission reduction and environmental pollution reduction. VOC in polyolefin materials are mainly alkanes and olefins, and some products contain a small amount of small molecule oxides, chlorides, benzene series, etc. If a component with good adsorption of volatile organic compounds is added to the resin, the VOC content released by the material into the environment can be reduced to obtain a low-VOC resin material.
[0003] Nano silicon dioxide is currently the world's largest industrially produced nano powder material with the highest output. Nano SiO2 has attracted much attention due to its inorganic rigidity, high specific surface energy, and strong surface adsorption capacity. Adding a small amount of SiO2 to PP can change its structure and interface characteristics, improve the mechanical properties of the composite material such as tensile strength, impact strength and elongation at break, and play a role in heterogeneous nucleation, accelerating crystallization, and increasing the crystallization peak temperature during the PP crystallization process. However, since SiO2 is an inorganic component, it is difficult to disperse evenly in the polymer, which affects its application.
[0004] Activated carbon is a porous carbon-containing material mainly composed of graphite microcrystals. Due to its developed pore structure, specific surface area and excellent adsorption properties, it is widely used in many fields such as exhaust gas treatment and air purification.
[0005] The existing technology usually adopts carbon-based materials and SiO2 to prepare by simple mixing. The structural stability of the composite material obtained by this method is relatively poor, which restricts the further improvement of the material performance and affects its scope of use. Summary of the invention
[0006] In order to solve the problems in the prior art, the present invention proposes a carbon-based silica composite material, a high-impact and low-VOC resin composite material, and a preparation method and application thereof. The present invention uses a carbon source and a silicon source as raw materials, and in a liquid phase system, in situ synthesizes SiO2 on the carbon source to form a composite containing a carbon source and SiO2, and then undergoes hydrothermal carbonization to prepare a composite component containing SiO2 and activated carbon fiber. The carbon-based silica composite material prepared by the present invention has a very high specific surface area and excellent adsorption performance. When added to a resin as a filler, the VOC release of the material can be significantly improved, and at the same time, the impact resistance of the resin material can be improved.
[0007] One of the purposes of the present invention is to provide a carbon-based silica composite material, wherein the carbon-based silica composite material is a carbon-based silica composite material in which silica is loaded on the surface of activated carbon fibers.
[0008] In the carbon-based silicon dioxide composite material of the present invention, preferably,
[0009] The mass ratio of activated carbon fiber to silicon dioxide in the carbon-based silicon dioxide composite material is 10:1 to 2:1.
[0010] The second object of the present invention is to provide a method for preparing a carbon-based silicon dioxide composite material, comprising the following steps:
[0011] After in-situ synthesis of silicon dioxide on a carbon source matrix, high-temperature carbonization is performed to obtain a carbon-based silicon dioxide composite material; preferably, the high-temperature carbonization is performed by a hydrothermal carbonization method in a high-pressure reactor;
[0012] The carbon source matrix is selected from a modified carbon source obtained by modifying a carbon source with raw materials including a surfactant and an alkali;
[0013] It is preferably used for the preparation of the carbon-based silicon dioxide composite material described in any one of the purposes of the present invention.
[0014] In the method for preparing the carbon-based silicon dioxide composite material of the present invention, preferably, the following steps are included:
[0015] (1) mixing an organic solvent dispersion of a carbon source, a surfactant solution, and an alkali solution uniformly, soaking, solid-liquid separation, washing the solid, and vacuum drying to obtain a modified carbon source;
[0016] (2) uniformly dispersing the modified carbon source in an organic solvent to obtain a suspension;
[0017] (3) Adding a silicon source solution to the suspension, dispersing the solution uniformly, and then performing a hydrothermal reaction in a high-pressure reactor to obtain a carbon-based silica composite material.
[0018] In the method for preparing the carbon-based silicon dioxide composite material of the present invention, preferably,
[0019] In step (1),
[0020] The carbon source is selected from natural plant polymer materials, preferably, the carbon source is selected from at least one of cellulose and hemicellulose;
[0021] More preferably, the molecular weight of the plant natural polymer material is 0.5×10 4 ~2.0×10 5 and / or,
[0022] The surfactant in the surfactant solution is selected from at least one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium fatty alcohol sulfate, and sodium succinate sulfonate; and / or,
[0023] The alkali in the alkali solution is selected from at least one of sodium hydroxide, potassium hydroxide, urea and ammonia water; and / or,
[0024] The organic solvent in the organic solvent dispersion of the carbon source is at least one selected from ethanol, acetone, tetrahydrofuran and ethyl acetate.
[0025] In the method for preparing the carbon-based silicon dioxide composite material of the present invention, preferably,
[0026] In step (1),
[0027] The mass ratio of the carbon source to the surfactant is 1:1 to 100:1; and / or,
[0028] The mass ratio of the carbon source to the alkali in the alkali solution is 200:1 to 4:1; and / or,
[0029] The soaking time is 1-5 hours; the soaking of the present invention is carried out at room temperature;
[0030] Preferably,
[0031] The concentration of the surfactant solution is 0.5wt-20wt%; and / or,
[0032] The concentration of the alkali solution is 0.1wt%-5wt%.
[0033] In the method for preparing the carbon-based silicon dioxide composite material of the present invention, preferably,
[0034] In step (2),
[0035] The organic solvent is selected from at least one of ethanol, acetone, tetrahydrofuran and ethyl acetate; and / or,
[0036] The mass ratio of the modified carbon source to the organic solvent is 1:10 to 1:2.
[0037] In the method for preparing the carbon-based silicon dioxide composite material of the present invention, preferably,
[0038] In step (3),
[0039] The silicon source solution is selected from an organic solution of alkoxysilane; preferably,
[0040] The alkoxysilane in the silicon source solution is selected from at least one of tetraethyl silicate and tetramethyl orthosilicate; and / or,
[0041] The organic solvent in the silicon source solution is selected from at least one of ethanol, acetone, tetrahydrofuran and ethyl acetate; and / or,
[0042] The concentration of the silicon source solution is 0.5wt% to 10wt%; and / or,
[0043] The mass ratio of the alkoxysilane in the carbon source solution to the silicon source solution is 40:1 to 4.5:1.
[0044] In the method for preparing the carbon-based silicon dioxide composite material of the present invention, preferably,
[0045] In step (3),
[0046] adding a silicon source solution dropwise to the suspension; and / or,
[0047] The temperature of the hydrothermal reaction is 160-260°C; and / or,
[0048] The hydrothermal reaction time is 1-3 hours.
[0049] Further preferably, the present invention proposes an in-situ reaction of a solid material to prepare a carbon-based composite material loaded with silica in situ. The carbon source is selected from natural plant macromolecules, including cellulose, hemicellulose, etc. The cellulose is dispersed in an organic solvent, a surfactant and an alkaline solution are added, and solid-liquid separation is performed after mechanical stirring for uniform dispersion. The solid is washed with deionized water, and after vacuum drying, cellulose adsorbed with alkaline solution is prepared. The obtained solid is dispersed in an organic solution to obtain a cellulose suspension; a 0.01-0.1M tetraethyl silicate organic solution is prepared, and the solution is dripped into the uniformly stirred cellulose suspension, and white turbidity is generated in the system. The solution is transferred to a polytetrafluoroethylene reactor, and the reaction is heated at 160-260°C for 1-3 hours, and then naturally cooled to room temperature. The solid surface is ultrasonically cleaned with deionized water, and the solid is dried at a constant temperature of 60-80°C for 1-3 hours to obtain a carbon-based SiO2 composite material. The composite material is used for preparing a low-VOC polymer resin. Special impact-resistant PP pellets, 0.2wt% antioxidant and 0.5-10wt% carbon-based SiO2 composite material are uniformly mixed in a high-speed stirrer, the premixed uniform mixture is added to a co-rotating twin-screw extruder, extruded and granulated at 185-210°C to obtain a composite resin material, and dried at 80°C for 1-3h to obtain a low-VOC PP resin.
[0050] As can be seen from the above, the present invention uses a carbon source and a silicon source as raw materials, in a liquid phase system, in situ synthesizes a composite containing a carbon source (such as cellulose) and SiO2, and then undergoes hydrothermal carbonization to prepare a composite component containing SiO2 and activated carbon fiber. By using a carbon source dispersion system that absorbs alkali liquid, SiO2 particles are synthesized in situ on the surface of the carbon source. The in situ prepared carbon-based SiO2 composite material has a very high specific surface area and excellent adsorption performance. It is added to the resin as a filler, which can significantly improve the VOC release of the material and at the same time improve the impact resistance of the resin material.
[0051] The third object of the present invention is to provide a carbon-based silica composite material as described in any one of the objects of the present invention or a carbon-based silica composite material prepared by the method described in any one of the second objects of the present invention as a resin filler; preferably as a high-impact, low-VOC resin filler; more preferably as a high-impact, low-VOC polypropylene resin filler.
[0052] A fourth object of the present invention is to provide a high-impact and low-VOC resin composite material, wherein the filler used in the resin composite material is selected from the carbon-based silica composite material described in any one of the first objects of the present invention or the carbon-based silica composite material prepared by the method described in any one of the second objects of the present invention;
[0053] Preferably,
[0054] In the high-impact and low-VOC resin composite material, the filler content is 0.5-10wt%.
[0055] The fifth object of the present invention is to provide a method for preparing a high-impact low-VOC resin composite material, wherein the resin pellets, antioxidant and filler are uniformly mixed and then added to a twin-screw extruder, extruded into pellets, and dried to obtain the high-impact low-VOC resin composite material;
[0056] The filler is selected from the carbon-based silica composite material described in any one of the purposes of the present invention or the carbon-based silica composite material prepared by the method described in any one of the purposes of the present invention;
[0057] Preferably, the method is used for preparing the high-impact, low-VOC resin composite material described in the fourth objective of the present invention.
[0058] In the method for preparing the high-impact and low-VOC resin composite material of the present invention, preferably,
[0059] The antioxidant is selected from at least one of antioxidant 168, antioxidant 1076, and antioxidant 1010; preferably, the antioxidant is selected from antioxidant 168 or a compound of antioxidant 168 and at least one of antioxidant 1076 and antioxidant 1010; and / or,
[0060] The resin pellets are selected from polypropylene resin pellets; and / or,
[0061] The antioxidant content in the high-impact, low-VOC resin composite material is 0.05wt%-0.2wt%; and / or,
[0062] The filler content in the high-impact, low-VOC resin composite material is 0.5-10wt%; and / or,
[0063] The temperature of extrusion granulation is 185-210°C; and / or,
[0064] The twin-screw extruder is selected from a co-rotating twin-screw extruder.
[0065] The carbon-loaded material prepared by the hydrothermal method of the present invention can enhance the adsorption of the system, increase the specific surface area, and improve its adsorption performance. The present invention proposes an in-situ reaction of a solid material, synthesizes SiO2 in-situ on the surface of cellulose, and simultaneously prepares a cellulose-SiO2 composite material, and then undergoes hydrothermal carbonization to obtain a carbon-based SiO2 composite material. The composite material can be used to absorb VOC released by polymer resins, and can prepare resin composite materials with low VOCs. At the same time, the composite material has the characteristics of inorganic rigidity and can enhance the impact resistance of the resin.
[0066] The endpoints and any values of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values. For numerical ranges, the endpoint values of each scope, the endpoint values of each scope and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article.
[0067] Compared with the prior art, the present invention has at least the following advantages:
[0068] The present invention utilizes a carbon source (such as cellulose) dispersion system that absorbs alkali solution to in-situ synthesize SiO2 particles on the cellulose surface. The in-situ prepared carbon-based SiO2 composite material has a very high specific surface area and excellent adsorption performance. Adding it to the resin as a filler can significantly improve the VOC release of the material and at the same time improve the impact resistance of the resin material.
[0069] The carbon-based silicon dioxide composite material of the present invention has the characteristics of rigidity of inorganic materials and can enhance the impact resistance of resin.
[0070] The cellulose used in the present invention has the characteristics of abundant sources, good biocompatibility, stable physical and chemical properties, etc. The carbon material prepared with cellulose biomass as a precursor has a porous structure, low cost, and is environmentally friendly. It has great application prospects in the fields of environmental protection and materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0071] Figure 1 It is the total ion current chromatogram of volatile organic compounds of the original high-impact PP by headspace-GC-MS;
[0072] Figure 2 is the total ion current chromatogram of volatile organic compounds of pp in Example 1 by headspace-gas chromatography-mass spectrometry;
[0073] Figure 3 is the total ion current chromatogram of volatile organic compounds of pp in Example 2 by headspace-GC-MS;
[0074] Figure 4 is the total ion current chromatogram of volatile organic compounds of pp in Example 3 by headspace-GC-MS;
[0075] Figure 5 The headspace-GC-MS total ion current chromatogram of volatile organic compounds of pp in Comparative Example 1;
[0076] Figure 6 This is the total ion current chromatogram of the volatile organic compounds of pp in Comparative Example 2 by headspace-gas chromatography-mass spectrometry. DETAILED DESCRIPTION
[0077] The present invention is described in detail below in conjunction with specific drawings and embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.
[0078] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0079] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.
[0080] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0081] Source of raw materials:
[0082] In the following examples, the reagents used are all commercially available chemicals of analytical grade;
[0083] The special impact-resistant PP granules used are polypropylene resin granules, brand PPH-Y24.
[0084] The molecular weight of cellulose is 1.0×10 5 .
[0085] Test method:
[0086] In the following examples, the VOC of the materials was quantitatively determined by Agilent 7890A-5975C GC / MS and G1888A headspace sampler.
[0087] The following materials were subjected to VOC quantitative testing under the following conditions:
[0088] Headspace sampler conditions: sample 1.0 g, headspace heating temperature 120 °C, insulation 60 min.
[0089] Chromatographic conditions: HP-5MS gas chromatography column (30m×0.25mm×0.25μm), programmed temperature.
[0090] Mass spectrometry conditions: EI ionization source, full scan, m / z 20-500.
[0091] The quantitative method uses isomeric nonane as the standard and draws an external standard curve for quantitative calculation.
[0092] The mechanical properties of the materials are tested according to the following standards:
[0093] MFR is tested according to standard GB / T 3682.1-2018, temperature is 230℃, load is 2.16kg;
[0094] The tensile properties are tested according to the standard GB / T 1040-2006, and the tensile rate is 50mm / min;
[0095] Bending properties are tested according to standard GB / T 9341-2008;
[0096] The simply supported beam notched impact strength is tested according to the standard GB / T 1043.1-2008;
[0097] The heat deformation temperature is tested according to the standard GB / T 1634.1-2004.
[0098] Example 1
[0099] The carbon-based SiO2 composites were prepared as follows:
[0100] Step (1): 5.0 g of cellulose was dispersed in 20 mL of ethanol, 20 mL of a 5 wt% aqueous solution of sodium dodecylbenzene sulfonate surfactant and 20 mL of a 1 wt% aqueous solution of urea were added, and the mixture was stirred thoroughly. After being uniformly dispersed, the mixture was soaked for 3 hours, and then solid-liquid separation was performed. The solid was washed with deionized water, and vacuum dried at 60° C. for 2 hours to obtain modified cellulose.
[0101] Step (2) dispersing the solid (modified cellulose) obtained in step 1 in 100 mL of ethanol and stirring at high speed to obtain a uniformly dispersed cellulose suspension;
[0102] Step (3): Prepare an ethanol solution of TEOS (tetraethoxysilane): disperse 0.55 mL of TEOS in 50 mL of ethanol for later use;
[0103] Step (4): Preparation of carbon-based SiO2 composite material: slowly drop the TEOS ethanol solution prepared in step 3 into the uniformly stirred cellulose suspension prepared in step 2, and after high-speed stirring, transfer the solution to a high-pressure reactor. After reacting at 200°C for 2 hours, cool to room temperature, separate the solid and liquid, and clean the solid with deionized water ultrasonically.
[0104] Step (5): The solid obtained in step 4 is dried at a constant temperature of 80° C. for 2 hours to obtain a carbon-based SiO 2 composite material.
[0105] The low VOC polymer resin was prepared as follows:
[0106] Step (6): Mix the impact-resistant PP pellets, 0.2wt% 168 antioxidant and 3wt% carbon-based SiO2 composite material in a high-speed stirrer, add the premixed mixture into a co-rotating twin-screw extruder, extrude and granulate at 185-210°C to obtain a PP composite resin material, and dry it at 80°C for 2h to obtain a low-VOC PP resin.
[0107] Example 2
[0108] The carbon-based SiO2 composites were prepared as follows:
[0109] Step (1): 5.0 g of cellulose was dispersed in 20 mL of ethanol, 20 mL of a 5 wt% aqueous solution of sodium dodecylbenzene sulfonate surfactant and 20 mL of a 1 wt% aqueous solution of urea were added, and the mixture was stirred thoroughly. After being uniformly dispersed, the mixture was soaked for 3 hours, and then solid-liquid separation was performed. The solid was washed with deionized water, and vacuum dried at 60° C. for 2 hours to obtain modified cellulose.
[0110] Step (2) dispersing the solid obtained in step 1 in an ethanol solution and stirring at high speed to obtain a cellulose suspension;
[0111] Step (3): Prepare TEOS ethanol solution: dissolve 1.1 mL TEOS in 50 mL ethanol for later use.
[0112] Step (4): Preparation of carbon-based SiO2 composite material: slowly drop the TEOS ethanol solution prepared in step 3 into the uniformly stirred cellulose suspension prepared in step 2, and after high-speed stirring, transfer the solution to a high-pressure reactor, heat and react at 230°C for 1 hour, cool to room temperature, and ultrasonically clean the solid surface with deionized water;
[0113] Step (5): The solid obtained in step 4 is dried at a constant temperature of 60° C. for 1 hour to obtain a carbon-based SiO 2 composite material.
[0114] The low VOC polymer resin was prepared as follows:
[0115] Step (6): Mix the impact-resistant PP pellets, 0.2wt% antioxidant 168 and 3wt% carbon-based SiO2 composite material in a high-speed stirrer, add the premixed mixture into a co-rotating twin-screw extruder, extrude and granulate at 185-210°C to obtain a PP composite resin material, and dry it at 80°C for 2h to obtain a low-VOC PP resin.
[0116] Example 3
[0117] The carbon-based SiO2 composites were prepared as follows:
[0118] Step (1): 5.0 g of cellulose was dispersed in 20 mL of ethanol, 20 mL of a 5 wt% aqueous solution of sodium dodecylbenzene sulfonate surfactant and 20 mL of a 1 wt% aqueous solution of NaOH were added, and the mixture was stirred thoroughly. After being uniformly dispersed, the mixture was soaked for 3 hours, and then solid-liquid separation was performed. The solid was washed with deionized water, and vacuum dried at 60° C. for 2 hours to obtain modified cellulose.
[0119] Step (2) dispersing the solid obtained in step 1 in 100 mL of ethanol solution and stirring at high speed to obtain a cellulose suspension;
[0120] Step (3): Prepare TEOS ethanol solution: dissolve 0.22 mL TEOS in 50 mL ethanol for later use.
[0121] Step (4): Preparation of carbon-based SiO2 composite material: Slowly drop the TEOS ethanol solution prepared in step 3 into the evenly stirred cellulose suspension prepared in step 2. After high-speed stirring, transfer the solution to a high-pressure reactor and heat the reaction at 200°C for 1 hour. Cool to room temperature and ultrasonically clean the solid surface with deionized water.
[0122] Step (5): The solid obtained in step 4 is dried at a constant temperature of 80° C. for 1 hour to obtain a carbon-based SiO 2 composite material.
[0123] The low VOC polymer resin was prepared as follows:
[0124] Step (6): Mix the impact-resistant PP pellets, 0.2wt% antioxidant 168 and 3wt% carbon-based SiO2 composite material in a high-speed stirrer, add the premixed mixture into a co-rotating twin-screw extruder, extrude and granulate at 185-210°C to obtain a PP composite resin material, and dry it at 80°C for 2h to obtain a low-VOC PP resin.
[0125] The composition of the carbon-based silicon dioxide composite material prepared in the embodiment of the present invention is obtained by testing with an X-ray fluorescence element analyzer, as shown in Table 1 below.
[0126] Table 1. Composition of carbon-based silica composites
[0127] Example Mass ratio of activated carbon fiber / silicon dioxide Example 1 6:1 Example 2 2:1 Example 3 9:1
[0128] Comparative Example 1
[0129] The carbon-based SiO2 composites were prepared as follows:
[0130] Step (1): 5.0 g of cellulose was dispersed in 20 mL of ethanol, 20 mL of a 5 wt% aqueous solution of sodium dodecylbenzene sulfonate surfactant and 20 mL of a 1 wt% aqueous solution of NaOH were added, the mixture was stirred and evenly dispersed, and then soaked for 3 hours, followed by solid-liquid separation. The solid was washed with deionized water, and vacuum dried at 60° C. for 2 hours to obtain modified cellulose;
[0131] Step (2): dispersing the solid obtained in step 1 in 100 mL of ethanol solution and stirring at high speed to obtain a cellulose suspension;
[0132] Step (3): The cellulose suspension prepared in step 2 is transferred to a high-pressure reactor, heated at 200°C for 1 hour, cooled to room temperature, and the solid surface is ultrasonically cleaned with deionized water to obtain carbonized cellulose. SiO2 (SiO2 prepared in Comparative Example 3 below) is added in a ratio of 9:1 of the mass ratio of carbonized cellulose to silicon dioxide, and mechanically mixed to obtain a carbon-based SiO2 composite material.
[0133] The low VOC polymer resin was prepared as follows:
[0134] Step (4): Mix the impact-resistant PP pellets, 0.2wt% 168 antioxidant and 3wt% carbon-based SiO2 composite material in a high-speed stirrer, add the premixed mixture into a co-rotating twin-screw extruder, extrude and granulate at 185-210°C to obtain a PP composite resin material, and dry it at 80°C for 2h to obtain a low-VOC PP resin.
[0135] Comparative Example 2
[0136] The carbon-based materials were prepared as follows:
[0137] Step (1): 5.0 g of cellulose was dispersed in 20 mL of ethanol, 20 mL of a 5 wt% aqueous solution of sodium dodecylbenzene sulfonate surfactant and 20 mL of a 1 wt% aqueous solution of NaOH were added, the mixture was stirred and mixed thoroughly, and then the mixture was soaked for 3 hours, followed by solid-liquid separation. The solid was washed with deionized water, and vacuum dried at 60° C. for 2 hours to obtain modified cellulose;
[0138] Step (2): dispersing the solid obtained in step 1 in 100 mL of ethanol solution and stirring at high speed to obtain a cellulose suspension;
[0139] Step (3): The cellulose suspension of step 2 is transferred to a high-pressure reactor, heated at 200°C for 1 hour, cooled to room temperature, ultrasonically cleaned with deionized water, and dried at 80°C for 1 hour to obtain a carbon-based material.
[0140] The low VOC polymer resin was prepared as follows:
[0141] The impact-resistant PP pellets, 0.2wt% antioxidant 168 and 3wt% carbon-based material are mixed evenly in a high-speed mixer, and the premixed mixture is added into a co-rotating twin-screw extruder, extruded and granulated at 185-210°C to obtain a PP composite resin material, which is dried at 80°C for 2h to obtain a PP resin.
[0142] Comparative Example 3
[0143] Step (1): Prepare TEOS ethanol solution: dissolve 0.22 mL TEOS in 50 mL ethanol for later use.
[0144] Step (2): Preparation of SiO2 material: The TEOS ethanol solution prepared in step (1) and 1000 mL of ethanol were transferred to a high-pressure reactor, heated at 200° C. for 1 hour, cooled to room temperature, and the solid surface was ultrasonically cleaned with deionized water.
[0145] Step (3): Dry the solid obtained in step (2) at a constant temperature of 80° C. for 1 hour to obtain SiO2 material.
[0146] The low VOC polymer resin was prepared as follows:
[0147] The impact-resistant PP pellets, 0.2wt% antioxidant 168 and 3wt% SiO2 material are mixed evenly in a high-speed stirrer, the premixed mixture is added into a co-rotating twin-screw extruder, extruded and granulated at 185-210°C to obtain a PP composite resin material, and dried at 80°C for 2h to obtain a PP resin.
[0148] The VOC test and quantitative calculation results of the resin composite materials prepared in the embodiments of the present invention and the comparative examples are shown in Table 2 below. The corresponding volatile organic compound headspace-gas chromatography-mass spectrometry total ion current chromatograms are shown in Table 2 below. Figure 1 , Figure 2 , Figure 3 , Figure 4 , Figure 5 and Figure 6 shown.
[0149] Table 2. VOC test and quantitative calculation results of all samples
[0150]
[0151] The mechanical property test results of the resin composite materials prepared in the examples of the present invention and the comparative examples are shown in Table 3 below.
[0152] Table 3. Mechanical properties test results of samples
[0153]
[0154] By comparing the results of Example 3 and Comparative Example 1, it can be seen that only the composite containing a carbon source and SiO2 synthesized in situ in the present invention and then subjected to hydrothermal carbonization to prepare a composite component containing SiO2 and activated carbon fiber has a more superior adsorption performance, and adding it as a filler to the resin can more significantly improve the VOC release of the material and better improve the impact resistance of the resin material.
[0155] By comparing the results of Example 3, Comparative Example 1 and Comparative Example 2 and Comparative Example 3, it can be seen that the composite components containing SiO2 and activated carbon fibers prepared by the method of the present invention have a synergistic effect, and the two have more superior adsorption performance when used simultaneously. Adding them as fillers to the resin can more significantly improve the VOC release of the material and better improve the impact resistance of the resin material.
[0156] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.
[0157] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.
[0158] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.
[0159] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.
Claims
1. A carbon-based silicon dioxide composite material, characterized in that: The composite material is a carbon-based silicon dioxide composite material in which silicon dioxide is loaded on the surface of activated carbon fibers.
2. The carbon-based silicon dioxide composite material according to claim 1, characterized in that: The mass ratio of activated carbon fiber to silicon dioxide in the carbon-based silicon dioxide composite material is 10:1 to 2:
1.
3. A method for preparing a carbon-based silicon dioxide composite material according to any one of claims 1 to 2, characterized in that: The following steps are involved: After in-situ synthesis of silicon dioxide on a carbon source matrix, high-temperature carbonization is performed to obtain a carbon-based silicon dioxide composite material; preferably, the high-temperature carbonization is performed by a hydrothermal carbonization method in a high-pressure reactor; The carbon source matrix is selected from a modified carbon source obtained by modifying a carbon source with raw materials including a surfactant and an alkali.
4. The method for preparing the carbon-based silicon dioxide composite material according to claim 3, characterized in that: The following steps are involved: (1) mixing an organic solvent dispersion of a carbon source, a surfactant solution, and an alkali solution uniformly, soaking, solid-liquid separation, washing the solid, and vacuum drying to obtain a modified carbon source; (2) uniformly dispersing the modified carbon source in an organic solvent to obtain a suspension; (3) Adding a silicon source solution to the suspension, dispersing the solution uniformly, and then performing a hydrothermal reaction in a high-pressure reactor to obtain a carbon-based silica composite material.
5. The method for preparing the carbon-based silicon dioxide composite material according to claim 4, characterized in that: In step (1), The carbon source is selected from natural plant polymer materials, preferably, the carbon source is selected from at least one of cellulose and hemicellulose; Preferably, the molecular weight of the plant natural polymer material is 0.5×10 4 ~2.0×10 5 and / or, The surfactant in the surfactant solution is selected from at least one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium fatty alcohol sulfate, and sodium succinate sulfonate; and / or, The alkali in the alkali solution is selected from at least one of sodium hydroxide, potassium hydroxide, urea and ammonia water; and / or, The organic solvent in the organic solvent dispersion of the carbon source is selected from at least one of ethanol, acetone, tetrahydrofuran and ethyl acetate.
6. The method for preparing the carbon-based silicon dioxide composite material according to claim 4, characterized in that: In step (1), The mass ratio of the carbon source to the surfactant is 1:1 to 100:1; and / or, The mass ratio of the carbon source to the alkali in the alkali solution is 200:1 to 4:1; and / or, The soaking time is 1-5h; Preferably, The concentration of the surfactant solution is 0.5wt-20wt%; and / or, The concentration of the alkali solution is 0.1wt%-5wt%.
7. The method for preparing the carbon-based silicon dioxide composite material according to claim 4, characterized in that: In step (2), The organic solvent is selected from at least one of ethanol, acetone, tetrahydrofuran and ethyl acetate; and / or, The mass ratio of the modified carbon source to the organic solvent is 1:10 to 1:
2.
8. The method for preparing the carbon-based silicon dioxide composite material according to claim 4, characterized in that: In step (3), The silicon source solution is selected from an organic solution of alkoxysilane; Preferably, The alkoxysilane in the silicon source solution is selected from at least one of tetraethyl silicate and tetramethyl orthosilicate; and / or, The organic solvent in the silicon source solution is selected from at least one of ethanol, acetone, tetrahydrofuran and ethyl acetate; and / or, The concentration of the silicon source solution is 0.5wt% to 10wt%; and / or, The mass ratio of the alkoxysilane in the carbon source solution to the silicon source solution is 40:1 to 4.5:
1.
9. The method for preparing the carbon-based silicon dioxide composite material according to claim 4, characterized in that: In step (3), adding a silicon source solution dropwise to the suspension; and / or, The temperature of the hydrothermal reaction is 160-260°C; and / or, The hydrothermal reaction time is 1-3 hours.
10. Use of the carbon-based silica composite material as described in any one of claims 1 to 2 or the carbon-based silica composite material prepared by the method as described in any one of claims 3 to 9 as a resin filler; preferably as a high-impact, low-VOC resin filler; more preferably as a high-impact, low-VOC polypropylene resin filler.
11. A high-impact, low-VOC resin composite material, characterized in that: The filler used in the resin composite material is selected from the carbon-based silica composite material according to any one of claims 1 to 2 or the carbon-based silica composite material prepared by the method according to any one of claims 3 to 9; Preferably, In the high-impact and low-VOC resin composite material, the filler content is 0.5-10wt%.
12. A method for preparing a high-impact, low-VOC resin composite material as claimed in claim 11, characterized in that: The resin granules, antioxidant and filler are mixed uniformly, extruded into granules, and dried to obtain the high-impact and low-VOC resin composite material.
13. The method for preparing a high-impact, low-VOC resin composite material according to claim 12, characterized in that: The antioxidant is selected from at least one of antioxidant 168, antioxidant 1076, and antioxidant 1010; preferably, the antioxidant is selected from antioxidant 168 or a compound of antioxidant 168 and at least one of antioxidant 1076 and antioxidant 1010; and / or, The resin pellets are selected from polypropylene resin pellets; and / or, The antioxidant content in the high-impact, low-VOC resin composite material is 0.05wt%-0.2wt%; and / or, The filler content in the high-impact, low-VOC resin composite material is 0.5-10wt%; and / or, The temperature of extrusion granulation is 185-210°C; and / or, The extrusion granulation adopts a twin-screw extruder, and the twin-screw extruder is preferably a co-rotating twin-screw extruder.
Citation Information
Patent Citations
Preparation method of activated carbon fiber-loaded ordered mesoporous silica composite material
CN107551999A
Preparation method of carbon fiber and silicon dioxide nanosphere synergically filled ultra-high molecular weight polyethylene wear-resistant material
CN107663328A
Carbon fiber / nanometer silicon dioxide compound as well as preparation method and application thereof
CN112210397A
Preparation method and application of carbon-based loaded zinc ferrite composite material
CN112387284A
Cellulosic fibres or filaments reinforced with inorganic particles and method for the production thereof
EP2889400A1